2020
DOI: 10.1109/tsp.2020.2967182
|View full text |Cite
|
Sign up to set email alerts
|

Sampling and Reconstruction of Bandlimited Signals With Multi-Channel Time Encoding

Abstract: Sampling is classically performed by recording the amplitude of the input at given time instants; however, sampling and reconstructing a signal using multiple devices in parallel becomes a more difficult problem to solve when the devices have an unknown shift in their clocks.Alternatively, one can record the times at which a signal (or its integral) crosses given thresholds. This can model integrateand-fire neurons, for example, and has been studied by Lazar and Tóth under the name of "Time Encoding Machines".… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…We extended the work to understand single-signal Mchannel time encoding by building on the approach that Lazar and Tóth developed [3]. We showed that if such a 2Ωbandlimited, c-bounded signal x(t) is sampled noiselessly using M IF-TEMs with the same parameters κ, δ and b but with nonzero shifts between their integrators α (j) , j = 1 · · · M , then x(t) can be reconstructed from its samples t [9]. Essentially, if a 2Ω-bandlimited signal can be reconstructed using one TEM, then a 2M Ω-bandlimited signal can be reconstructed using M TEMs with the same parameters.…”
Section: Previous Workmentioning
confidence: 99%
See 3 more Smart Citations
“…We extended the work to understand single-signal Mchannel time encoding by building on the approach that Lazar and Tóth developed [3]. We showed that if such a 2Ωbandlimited, c-bounded signal x(t) is sampled noiselessly using M IF-TEMs with the same parameters κ, δ and b but with nonzero shifts between their integrators α (j) , j = 1 · · · M , then x(t) can be reconstructed from its samples t [9]. Essentially, if a 2Ω-bandlimited signal can be reconstructed using one TEM, then a 2M Ω-bandlimited signal can be reconstructed using M TEMs with the same parameters.…”
Section: Previous Workmentioning
confidence: 99%
“…In previous work, the constraints for reconstructability were written in terms of the bandwidth Ω, the signal bound c, and the parameters of the TEMs κ, δ and b [3,9,10,11,13]. These constraints arise because of a relationship between the spiking rate of each machine r (j) and the parameters of the machine.…”
Section: Conditions For Reconstructibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…[8,9]. Time encoding systems have been previously used for reconstructing signals in shift-invariant spaces [10][11][12][13][14][15], as well as FRI signals in [16][17][18][19] using exponential spline sampling kernels and in [20] using hyperbolic secant kernels.…”
Section: Introductionmentioning
confidence: 99%